2015
DOI: 10.1186/s13104-015-1600-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge seeking behaviours of pre interns and early career doctors in Sri Lanka: a cross sectional study

Abstract: BackgroundUse of reference sources for medical knowledge has changed dramatically over the last two decades with the introduction of online sources of information. This study analyses the medical knowledge seeking behaviours of pre interns and early career doctors in Sri Lanka.MethodsThis cross sectional survey with a convenience sample was conducted at two sites targeting two groups; pre-intern doctors graduated from the Faculty of Medicine, University of Colombo and early career doctors following a postgradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…UpToDate has been shown to answer clinical questions effectively, with one study citing an 86% answer retrieval rate for UpToDate 10 . In medical education, UpToDate is reported to be a highly effective resource for learning 11 and is preferred by early career doctors 12 .…”
Section: About Uptodatementioning
confidence: 99%
“…UpToDate has been shown to answer clinical questions effectively, with one study citing an 86% answer retrieval rate for UpToDate 10 . In medical education, UpToDate is reported to be a highly effective resource for learning 11 and is preferred by early career doctors 12 .…”
Section: About Uptodatementioning
confidence: 99%
“… 15 Use of UpToDate®, a clinical decision-making support tool with over 11,800 clinical topics peer-refereed by more than 7,300 authors and editors, has been shown to improve clinical outcomes, 16 , 17 increase provider efficiency, 15 , 18 and enhance medical education. 19 More than 2 million clinicians and other healthcare professionals in 190 countries rely on UpToDate® for routine clinical reference; In the United States, two-thirds of hospitals and health systems and 90% of teaching hospitals routinely use UpToDate®. 20 Given the near ubiquitous use of this medical resource among trainees and senior clinicians, we must have a clear understanding of how race is used in reference articles in order to ensure we do not exacerbate racial health inequities.…”
Section: Introductionmentioning
confidence: 99%
“…Some trials have shown that articles randomly selected to be shared on social medial did not show a change in 30-day page views (15,16). Although the majority of health professionals use technology to access information, the challenges of keeping up to date with the overwhelming dispersion of information and the barriers to information seeking, such as time constraints and inadequate information and communication technology infrastructure, have been well described (4,8,(17)(18)(19)(20)(21). However, there is limited understanding about clinicians' and researchers' perspectives on how different forms of communication affect the way that they access, consume, and translate scientific information into clinical practice or research.…”
Section: Introductionmentioning
confidence: 99%